Long-distance coherent secure communication network based on synchronized chaotic semiconductor lasers - Du, Zhounan; Yang, Wenyan; Chen, Jianjun; Wang, Fei; Lin, Xiaodong; Wang, Yu; Zhong, Haibin; Deng, Tianjie; Deng, Tao (Applied optics. Optical technology and biomedical optics, 2025)
In this paper, we propose and numerically investigate a long-distance coherent secure communication network scheme based on a synchronized chaotic semiconductor laser. The central driving laser (CDL) with optical feedback can achieve chaotic signals with enhanced bandwidth and suppressed time delay signature through a dispersion component and a phase modulator, and high-quality chaos synchronization and communication between two arbitrary response lasers (RLs, legal receivers) can be guaranteed due to the identical injection from CDL. After adopting coherent detection and the modified constant modulus algorithm (MCMA) to compensate for the fiber transmission impairments, including chromatic dispersion and nonlinear effects, we demonstrate a bidirectional 64 Gb/s 16-quadrature amplitude modulation (16-QAM) message transmission over 800 km with a bit-error rate (BER) below the hard-decision forward-error-correction threshold of 3.8×10 . Additionally, the communication performance of this proposed system under different message transmission rates, launch powers, transmission distances, and typical parameter mismatches is discussed.